Fine-scale dynamics of fragmented aurora-like emissions - D. K. Whiter (Copernicus Publications, 2021)
Fragmented aurora-like emissions (FAEs) are small (few kilometres) optical structures which have been observed close to the poleward boundary of the aurora from the high-latitude location of Svalbard (magnetic latitude 75.3 ∘N). The FAEs are only visible in certain emissions, and their shape has no magnetic-field-aligned component, suggesting that they are not caused by energetic particle precipitation and are, therefore, not aurora in the normal sense of the word. The FAEs sometimes form wave-like structures parallel to an auroral arc, with regular spacing between each FAE. They drift at a constant speed and exhibit internal dynamics moving at a faster speed than the envelope structure. The formation mechanism of FAEs is currently unknown.